Tantangan Tenaga Pendidik Dalam Proses Pembelajaran di Sekolah Dasar Swasta Santa Maria Tarutung - Situmorang, Tiur Era Sanita; Selly nainggolan; Inriyanti simamora; Dodi irwanto siburian (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This paper discusses the results of observations of teaching staff at Santa Maria Tarutung Private Elementary School. Observations were carried out over two days, focusing on learning methods, teacher-student interactions, and classroom management. Observation results show that the teaching staff at Santa Maria Tarutung Private Elementary School have good competence in teaching and guiding students. They use various interesting and interactive learning methods, and are able to establish good relationships with students. Apart from that, they are also able to manage the class well, thereby creating a conducive learning atmosphere.